Anxiety, Desperation, Coping Strategies and Self- Efficacy as Predictors of Superstitious Behavior - Ankita (My University, 2022)
Every country, region, religion, and even an individual household has its own set of superstitions. Superstitions can even vary from person to person. Sometimes superstitions can have a comforting consequence, which can relieve anxiety about the unknown and provide people the feeling of control over their lives. This may be the ground as to why superstitions are into existence for so long — as they have been passed on from generation to generation. The same goes for desperation. Desperation makes people weak, and it leads to rash decisions. Everyone copes in their own way with the stressors, and the coping strategies also differ from person to person. So, through this research, efforts were made to find if anxiety and desperation encourage superstitious behavior in people and if there is any relation between coping strategies, self-efficacy, and superstition. For the study, eight hypotheses were formed. A total of 194 adults were used for the research through the purposive sampling. We found that anxiety and desperation are positively related to the superstitious behavior and emotion-focused and avoidant coping was also positively associated with superstition.
Keywords: superstitious beliefs; coping style; anxiety; desperation; self-efficacy